2013
DOI: 10.1542/peds.2012-0643
|View full text |Cite
|
Sign up to set email alerts
|

Playground Safety and Quality in Chicago

Abstract: OBJECTIVES: To assess playground safety and quality in Chicago, Illinois, identify disparities in access, and use the data to inform collaborative improvement. METHODS: A cross-sectional survey of public park playgrounds in Chicago, Illinois, was conducted in 2009, 2010, and 2011 by using the National Program for Playground Safety Standardized Survey. All playgrounds were surveyed in 2009 and 2010; those that failed in 2010 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Disparities were also found with regard to race/ethnicity, with AfricanAmerican and Hispanic children more likely to live in neighborhoods with unsafe playgrounds or fewer playgrounds, respectively. 1 These findings are consistent with other research on this topic. 4,5 Like most areas of public health, the field of pediatric injury is not immune to disparity.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Disparities were also found with regard to race/ethnicity, with AfricanAmerican and Hispanic children more likely to live in neighborhoods with unsafe playgrounds or fewer playgrounds, respectively. 1 These findings are consistent with other research on this topic. 4,5 Like most areas of public health, the field of pediatric injury is not immune to disparity.…”
supporting
confidence: 90%
“…The authors found that among playgrounds utilizing wood chips for safety surfacing, up to 99% failed to meet minimum safety recommendations for chip depth. 1 The two determinants of energy transfer in a fall are (1) fall height and (2) the impact attenuating capacity of the surface. Adequate safety surfacing is critically important for the prevention of playground-related injuries.…”
mentioning
confidence: 99%
“…The impact depends on the height of fall, which can happen in a playground toy or from windows or roofs [17][18][19][20][21][22][23] . In the present series high height falls were associated with severity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…10, No. 22; safety (Allen et al, 2012;Doaa, 2012;Wheway, 2012;Howard et al, 2009;Mott et al, 1997;Beugels, 1993;Bond & Peck, 1993). Further explanation will be discussed in the result and discussion section…”
Section: Surfacing Materialsmentioning
confidence: 98%